circAGFG1 sponges miR-28-5p to promote non-small-cell lung cancer progression through modulating HIF-1α level - Ma Xiaoan (De Gruyter, 2021)
Circular RNAs (circRNAs) have gained much attention for their crucial regulatory roles in human diseases and cancers. However, the role and the mechanism of circRNA ArfGAP with FG repeats 1 (circAGFG1) in non-small-cell lung cancer (NSCLC) are still largely unknown. circAGFG1 was highly expressed in NSCLC, and high expression of circAGFG1 was closely related to the low survival rate of NSCLC patients. circAGFG1 knockdown inhibited the proliferation, migration, and invasion and promoted the apoptosis of NSCLC cells. circAGFG1 bound to miR-28-5p in NSCLC cells, and circAGFG1 promoted NSCLC progression partly through sponging miR-28-5p in vitro. HIF-1α was a target of miR-28-5p, and miR-28-5p overexpression-mediated influences in NSCLC cells were partly overturned by the addition of HIF-1α overexpression plasmid. circAGFG1/miR-28-5p/HIF-1α axis regulated cellular glycolytic metabolism in NSCLC cells. circAGFG1 silencing restrained the xenograft tumor growth in vivo. circAGFG1 promoted the proliferation, migration, and invasion and suppressed the apoptosis of NSCLC cells through accelerating the glycolysis via miR-28-5p/HIF-1α axis.